2006
DOI: 10.1063/1.2338829
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in acoustic properties of ferroelectric relaxor Pb[(Zn1∕3Nb2∕3)0.955Ti0.045]O3 single crystals studied by Brillouin and dielectric spectroscopies

Abstract: Acoustic and dielectric properties of Pb͓͑Zn 1/3 Nb 2/3 ͒ 1−x Ti x ͔O 3 ͑PZN-xPT͒ single crystals with x = 0.045 have been studied by the high-resolution micro-Brillouin scattering and dielectric spectroscopy in a wide temperature range. The softening of the Brillouin shift and the increase of dielectric relaxation time upon cooling indicated the formation of polar nanoregions ͑PNRs͒ and the slowing down of their dynamics. In contrast to the acoustic properties of typical model relaxors such as lead magnesioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Small elastic hysteresis between cooling and heating of unpoled PZN-4.5%PT through the t ↔ c transition has been observed previously 28 and is typical of first-order transitions. Some elastic hysteresis between poled and unpoled crystals was also expected since the bulk piezoelastic properties of a preferential alignment of t or r domains will differ from those of a crystal with randomly oriented domains.…”
Section: Discussionsupporting
confidence: 71%
“…Small elastic hysteresis between cooling and heating of unpoled PZN-4.5%PT through the t ↔ c transition has been observed previously 28 and is typical of first-order transitions. Some elastic hysteresis between poled and unpoled crystals was also expected since the bulk piezoelastic properties of a preferential alignment of t or r domains will differ from those of a crystal with randomly oriented domains.…”
Section: Discussionsupporting
confidence: 71%
“…The dynamical aspects of the PNRs have been extensively studied in the prototype RFEs such as Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) and Pb(Zn 1/3 Nb 2/3 )O 3 (PZN) and other related systems through Brillouin light scattering studies [11][12][13][14][15][16][17]. Raman scattering studies revealed the existence of the intermediate temperature T…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Extensive studies of the dynamical aspects of PNRs have been carried out with the PMN-PT, PZN-PT, and Pb(Ni 1=3 Nb 2=3 )O 3 -PT systems through neutron and light scattering studies. [11][12][13][14][15][16][17] Brillouin scattering studies in these systems revealed many interesting features of PNRs such as the softening of the acoustic phonon mode and the appearance of a central peak (CP) below T B and the slowing down of relaxation time and the coupling between the polarization and local strain fluctuations. [14][15][16][17] The 1 : 1 type ferroelectric materials Pb(B 0 1=2 B 00 1=2 )O 3 are of special interest because their degree of ordering can be controlled by thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Brillouin scattering studies in these systems revealed many interesting features of PNRs such as the softening of the acoustic phonon mode and the appearance of a central peak (CP) below T B and the slowing down of relaxation time and the coupling between the polarization and local strain fluctuations. [14][15][16][17] The 1 : 1 type ferroelectric materials Pb(B 0 1=2 B 00 1=2 )O 3 are of special interest because their degree of ordering can be controlled by thermal treatment. Pb(In 1=2 Nb 1=2 )O 3 (PIN) belongs to a class of Pb(B 0 1=2 B 00 1=2 )O 3 compounds that exhibit interesting dielectric properties depending on the degree of B site ordering.…”
Section: Introductionmentioning
confidence: 99%